Analysis of the concept of istitho'ah in the Hajj bailout fund - Muhammad Arsy (Asy-Syari’ah : Jurnal Hukum Islam, 2026)
This study aims to analyze the problems of the implementation of hajj bailout funds in Indonesia through a review of the concept of istitho'ah (ability). The phenomenon of long hajj queues has triggered financial institutions to offer instant financing schemes that have the potential to obscure the essence of financial independence in worship. Using the library research method, this article examines the classical jurisprudence literature on zad wa rahilah and synchronizes it with contemporary regulations such as DSN-MUI Fatwa Number 29 of 2002 and Law Number 8 of 2019. This study found that hajj bailout funds are legally permissible under the Qardh and Ijarah contracts. Nevertheless, from a philosophical perspective, the debt-based financing scheme tends to undermine the values of spiritual sacrifice and self-reliance in performing the hajj. The use of debt instruments in Hajj registration is seen as disrupting the stability of the national queue and creating a financial burden that is contrary to the principle of inner relief in worship. Therefore, a stricter policy reconstruction on access to bailout funds is needed to maintain the dignity of the hajj pilgrimage as an obligation for those who are truly able in real terms, not just administratively banking.